The Influence of Performance Expectancy, Effort Expectancy, and Social Influence on Behavioral Intentions among QRIS Users in Selopampang Community - Amin Nasrulloh; Ayu Nurhidayah (Yayasan Azhar Amanaa Yogyakarta, 2026)
The rapid development of technology, particularly in the field of financial technology, has provided various benefits in everyday life. One such innovation is QRIS, a digital payment service that facilitates cashless transactions. To assess the acceptance of QRIS among the Selopampang community, this study applies the Unified Theory of Acceptance and Use of Technology (UTAUT) to examine the effects of performance expectancy, effort expectancy, and social influence on users’ behavioral intentions to use QRIS. This study employed a quantitative descriptive approach using multiple linear regression analysis with SPSS 25. The sample consisted of 100 respondents selected through purposive sampling. The research instrument was tested for validity and reliability, followed by classical assumption tests, including normality, linearity, multicollinearity, and heteroscedasticity tests. Multiple linear regression analysis was then conducted using t-test, F-test, and coefficient of determination (R²). The results indicate that performance expectancy has a positive and significant effect on behavioral intentions. Similarly, effort expectancy and social influence each have a positive and significant effect on behavioral intentions. Simultaneously, performance expectancy, effort expectancy, and social influence have a positive and significant effect on behavioral intentions. The coefficient of determination (R²) indicates that the three independent variables collectively explain 50.5% of the variance in behavioral intentions to use QRIS.